Clonal diversity of Actinobacillus actinomycetemcomitans isolates from young adults with minimal periodontal disease - Macheleidt, Alexander; Müller, Hans-Peter; Eger, T.; Putzker, M.; Zöller, L. (Journal of periodontal research, 1999)
Actinobacillus actinomycetemcomitans is a major periodontal pathogen which is associated with both early-onset periodontitis and adult cases refractory to conventional periodontal therapy, although the organism has also been shown to be widely distributed among dentate healthy individuals. The observed disease status may be associated with a variation in virulence of different strains or clones. The aim of the present study was to analyse genotype distribution as assessed by an arbitrarily primed polymerase chain reaction (AP-PCR) among 51 isolates of A. actinomycetemcomitans recovered from more than 200 young adult recruits with no or minor periodontal disease. In addition, isolates from 25 periodontitis patients as well as reference strains were genotyped.